Molecular Evidence for the Presence of Borrelia burgdorferi and Anaplasma platys among Domesticated Animal Population-Study Based on Real Time PCR Methodology–in Thrissur District-Kerala, India - Karunakaran, Sunitha; Gopinathan, Gopika Thattat; Sasidharan, Hareesh (Newest Updates in Agriculture and Veterinary Science Vol. 3, 2023)
A very high prevalence of tick transmitted diseases is observed among domesticated animal population in Kerala now days. Conventional diagnostic methods based on microscopy will not be sufficient to identify spirochete like Borrelia burgdorferi and bacterium like Anaplasma platys. The present study was aimed to use Taqman based qualitative Real Time PCR (qPCR) as an aid to understand the presence of B. burgdorferi-bacterium causing Lyme disease and A. platys-bacterium affecting platelets, among our domesticated animal population. Previously reported, forward and reverse primers and probe sequences specific for A. platys (1) and B. burgdorferi (2) were used in the study. Results of the present study shows that almost all the domesticated animal species tested from both Wayanad and Thrissur districts were found to harbour either A. platys or Borrelia or both pathogens. Based on the qualitative detection of specific gene targets, qPCR can be reliably used as an aid in accurate and confirmatory diagnosis up to species level. To authors knowledge this is the first report for molecular evidence of the A. platys and B. burgdorferi among domesticated animal population in the state of Kerala which should be a major concern and requires further detailed investigation including more number of samples from different districts representing different geographical regions.